Isoniazid- and ethambutol-induced psychosis - Prasad R (Annals of Thoracic Medicine, 2008)
Most cases of antituberculous agent-associated psychoses were caused by isoniazid (INH), with ethambutol (EMB)-induced psychosis being rare. The concomitant occurrence of INH- and EMB- induced psychosis and in a single individual is extremely uncommon. We report a case of 28-year-old male who developed psychotic symptoms on start of EMB initially and later on INH also. He was prescribed rifampicin, pyrazinamide, and ofloxacin and had no further psychotic symptoms.